Pengaruh Media Quizizz terhadap Motivasi dan Prestasi Belajar Peserta Didik pada Mata Pelajaran IPS Materi Sumber Daya Alam Kelas VII SMP Kurikulum Merdeka di Kabupaten Banyumas - Nopidha Ardyansah (Proceedings Series on Social Sciences & Humanities, 2023)
Quizizz is a digital platform that is currently often used in learning activities. This application can be used as an alternative fun learning media for students. The purpose of this study was to determine the effect of Quiziz media on students' motivation and learning achievement in social studies learning. This study uses a quasi-experimental quantitative. The population for this study were junior high schools in the sub-rayon 1 area of Banyumas, while the samples were SMP Negeri 5 Purwokerto, SMP Negeri 7 Purwokerto dan SMP Muhammadiyah 2 Purwokerto. The sampling technique used purposive sampling with the consideration that the school is still in the working area of the researcher so that it makes it easier to do research. The results of this study on learning achievement showed that there was an interaction between groups and pre post scores (F= 6.549; sig < 0.05). It can be seen that there is a difference at the 5% level (t=4.192; p<0.05). This means that the experimental group has a significant change compared to the control group. The treatment given to the experimental group was declared successful. Based on the results of the effect size on cohens d, a point estimate value of 0.630 is obtained. This means that the effective contribution of giving treatment in increasing scores in the experimental group is 63%. As for student learning motivation, the results of the calculation are proven by the significance reference t test (0.001) <0.05, then H0 is rejected and Ha is accepted. This means that there are significant differences in student motivation between the control class and the experimental class. This shows that there is an effect of using Quizizz media on student learning motivation. Based on the results of the study it can be concluded that using Quizizz can encourage students' motivation in learning. so, students who are motivated in learning will be able to improve their learning achievement.